Pelatihan Komunikasi Bisnis Bagi Umkm - Amal, Muhammad Khairul (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2023)
Business communication training is one solution to the problems faced by MSMEs, namely lack of communication skills, effective marketing understanding, limited resources, lack of communication skills in the online world, difficulties in building business networks, lack of integrated communication strategies, and handling customer complaints. The purpose of this activity is to improve skills and understanding of MSMEs related to effective communication strategies. The method of implementing this activity is training for MSMEs in the Sukamekar Village environment of Sukabumi Regency. The partners in this training activity are the Cooperative and SME Office of Sukabumi Regency. The evaluation was carried out by giving questionnaires to trainees before and after delivering the material, and the result was that the ability and understanding of the participants increased by 39.29%.